2017
DOI: 10.18632/oncotarget.19390
|View full text |Cite
|
Sign up to set email alerts
|

Programmed death ligand-1 and MET co-expression is a poor prognostic factor in gastric cancers after resection

Abstract: Programmed death-ligand 1 (PD-L1) plays an essential protein for immune evasion, contributing to tumor development and progression. Recent studies have reported MET as an upregulator for PD-L1 overexpression through an oncogenic pathway. However, an association between PD-L1 expression with MET has not been reported in gastric cancer.The prognostic significance of PD-L1 and its association with Epstein-Barr virus (EBV), microsatellite instability (MSI), and mucin phenotype remain controversial.We performed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 44 publications
2
23
0
Order By: Relevance
“…Consistent with several previous published reports, an IHC score of ≥1+ was considered positive [11,15]. To evaluate the expression of MMR proteins, the following primary antibodies were used in this analysis: anti-MLH1 (pre-diluted; Ventana Medical Systems), anti-MLH2 (1:300; Cell Marque, Rocklin, CA, USA), anti-MSH6 (1:200; Cell Marque), and anti-PMS2 (prediluted; Ventana Medical Systems) antibodies.…”
Section: Immunohistochemistry Andmicrosatellite Status Determinationsupporting
confidence: 69%
See 2 more Smart Citations
“…Consistent with several previous published reports, an IHC score of ≥1+ was considered positive [11,15]. To evaluate the expression of MMR proteins, the following primary antibodies were used in this analysis: anti-MLH1 (pre-diluted; Ventana Medical Systems), anti-MLH2 (1:300; Cell Marque, Rocklin, CA, USA), anti-MSH6 (1:200; Cell Marque), and anti-PMS2 (prediluted; Ventana Medical Systems) antibodies.…”
Section: Immunohistochemistry Andmicrosatellite Status Determinationsupporting
confidence: 69%
“…Genomic DNA was extracted from 10-µm thick sections of 10% neutral manually dissected FFPE tumor tissue using the Maxwell ® 16 FFPE Puri cation Kit for DNA (Promega, USA). The mutations in the KRAS (exon 2 and 3), BRAF (exon 14), and PIK3CA (exon 9 and 20) genes were analyzed by directional sequencing of PCR fragments ampli ed from the genomic DNA as previously described [11]. All sequences were con rmed in duplicate for replicate ampli cation reactions.…”
Section: Mutation and Hpv Detection Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent decades, molecular biomarkers for gastric prognosis have been widely reported ( Arigami et al, 2013 ; Guo et al, 2013 ; Liu et al, 2015 ; Rachidi et al, 2013 ). PD-L1 and MET1 co-expression predicted a poor survival of gastric cancer, with shorter overall survival rate and disease-free survival rate ( Kwon et al, 2017 ). The low expression of BUB1 also suggested a poor prognosis ( Stahl et al, 2017 ), and EPHB4 showed a similar pattern for prognosis ( Yin et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…The PD-L1/PD-1 axis is reported to be driven by the oncogenic activation of the signaling pathways, such as the mitogen-activated protein kinase (MAPK) and PI3K pathways. Additionally, this axis is regulated by other factors in the tumor microenvironment, including microsatellite instability (MSI) caused by de cient mismatch repair (dMMR) and human papillomavirus (HPV) [9][10][11][12][13]. However, MSI/dMMR, RAS/BRAF/PIK3CA mutations, and HPV status have been rarely investigated in esophageal cancers.…”
Section: Introductionmentioning
confidence: 99%